Collective Identity Formation in Campus-Based Sexual Violence Prevention: : A Case Study of Girl Up UNS - Rizky Azzahra Amallia; Siany Indria Liestyasari (Faculty of Social Science, Universitas Negeri Malang, 2026)
This study analyzes the process of collective identity formation in Girl Up UNS as the foundation for sustaining sexual violence prevention efforts on campus, viewed through Alberto Melucci's New Social Movement theory. It employed a qualitative approach with a case study design. Ten informants were selected through purposive sampling, including the founder, former core board members (2022–2025), and active board members from various divisions. Data were collected through semi-structured in-depth interviews, non-participant observation of regular Bi-Weekly Meetings and campaign activities, and analysis of organizational documents from 20222025. Data were analyzed using Miles, Huberman, and Saldaña's interactive model, comprising data reduction, data display, and conclusion drawing, with validity ensured through technique and source triangulation. Findings show Girl Up UNS's collective identity forms through an ongoing negotiation process. Collective identity underpins the organization's sexual violence prevention education programs, while interactions and value negotiations during these activities continually strengthen and sustain that identity. Activism through gender literacy education, hotline services, and policy advocacy also challenges campus culture and bureaucracy. The study's novelty lies in the mutually reinforcing relationship between collective identity and collective action: identity drives action, while repeated action continues to build, strengthen, and sustain Girl Up UNS's collective identity as a student movement.